Plyometrics for speed and power : includes over 100 drills and exercises - Thurgood, Glen, ....- (Ramsbury : The Crowood Press Ltd, 2016)
Guiding you through the basics of plyometric training through to sport-specific drills, this new book covers the history of plyometrics and the science behind it; foundation strength; plyometric equipment; warm-up techniques and performance testing.
Keywords: Krachttraining